2013
DOI: 10.1371/journal.pone.0058214
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Lung Function Decline in Patients with Non-Tuberculous Mycobacterial Pulmonary Disease

Abstract: BackgroundThere is paucity of risk factors on lung function decline among patients with non-tuberculous mycobacteria (NTM) pulmonary disease in literature.MethodsPatients with NTM pulmonary disease between January 2000 and April 2011 were retrospectively selected. Sixty-eight patients had at least two pulmonary function tests within a mean follow-up period of 47 months.ResultsSixty-eight patients were included. They had a median age of 65 years and 65% had impaired lung function (Forced expiratory volume in 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…Lee et al found a substantial decline in lung function in young NTM patients. [26]. Their findings are consistent with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Lee et al found a substantial decline in lung function in young NTM patients. [26]. Their findings are consistent with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Alternatively, antibiotic therapy for pulmonary NTM may not sufficiently control the inflammation or maintain airway structure and function, and progressive airflow limitation may be the natural progression of disease. In order to accurately explore this issue, a larger cohort and longer observation period is necessary, including substantial numbers of patients in all groups (asthma, COPD, ‘normal’), as well as detailed information on both the nature and extent of radiological lung disease …”
Section: Discussionmentioning
confidence: 99%
“…Disease is frequently chronic despite prolonged multi‐drug therapy, secondary to difficulty in tolerating intensive therapy, an inability to eradicate the infection (sometimes due to drug resistance), and recurrence after apparently successful therapy . It is therefore important to identify patients at greater risk for clinical deterioration and provide optimal therapy to those patients …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of disease progression on the amount of muscle in patients with MAC pulmonary disease are not well recognized. We did not evaluate whether the muscle function, such as the grip strength, was decreased in the MAC patients; however we hypothesized that a decrease in the amount of muscle and the attenuation of muscle strength influence the patient's pulmonary function and the quality of life as the disease progresses (13,14).…”
Section: Discussionmentioning
confidence: 99%